Comparison of Postoperative Pain and Recovery between Single-Port and Two-Port Thoracoscopic Lobectomy for Lung Cancer - Liu, Zhengcheng; Yang, Rusong; Shao, Feng (The Thoracic and Cardiovascular Surgeon, 2019)
Objective To investigate whether the single-port (SP) technique had more favorable postoperative outcomes than had the two-port (TP) technique.Methods One hundred sixty-six single-port video-assisted thoracoscopic surgery (SP-VATS) lobectomy and 162 two-port video-assisted thoracoscopic surgery (TP-VATS) lobectomy had been successfully completed between August 2015 and September 2016. A single incision of ∼3 cm was made in an intercostal space along the anterior axillary line. Perioperative outcomes and the safety between SP-VATS and TP-VATS lobectomy for NSCLC was compared.Results In the SP-VATS group, incision size was kept to a minimum, with a median of 3 cm; mediastinal lymph node dissection was performed in all patients with malignancy. Overall, median operative time was 89 minutes, and median chest tube duration was 3.1 days. The VAS on postoperative days 3, 7, and 14 was less in the SP-VATS group than that in the TP-VATS group. The VAS on days 1, 30, 60, 90, 180, and 360 did not differ significantly between the two groups. The number of days of use of analgesic agents after surgery was less in the SP-VATS group. The pathological symptoms of wound pain were significantly less in the SP-VATS group.Conclusions Compared with the multiport approach, SP VATS lobectomy might reduce postoperative pain and lead to faster recovery.
Keywords: single-port; VATS; lobectomy; minimally invasive; lung cancer